Barriers and facilitators of male engagement in Community Client-Led Antiretroviral therapy Delivery groups (CCLADS) for HIV care and treatment in Southwestern Uganda: a qualitative study - Jovaile Kushemererwa; Moses Muwanguzi; Esther C. Atukunda; Halimah Nantambi Kikomeko; Odwee Ambrose; Denis Androdri; Brillian Kembabazi; Josephine Nambi Najjuma (BMC, 2022)
Abstract Background Male engagement in HIV programs is a persistent challenge that results in poor utilization of HIV care services. Differentiated service delivery models, such as Community Client-Led Antiretroviral Delivery Groups (CCLADs), provide an opportunity for male engagement in HIV care. In southwestern Uganda. In southwestern Uganda few men living with HIV (MLWHIV) are involved in CCLADS. We aimed to identify facilitators, barriers and perceptions to CCLADs enrollment by MLWHIV at ART Clinics in southwestern Uganda. Methods A qualitative study was conducted among MLWHIV who were registered and receiving ART at two ART Clinics/health facilities in southwestern Uganda, irrespective of their enrollment status into CCLADs. In-depth interviews (IDI) were conducted among recruited HIV positive men, and Key informant interviews (KIIs) among clinic in-charges and counselors, women enrolled in CCLADS using a semi-structured interview guide. We used thematic analysis to analyze the data from the interviews. Results We conducted 16 interviews, 7 KII and 8 IDI were conducted. MLWHIV and key informants shared the facilitators and barriers. Men who were not involved in CCLADs shared the barriers to joining the CCLADs. The themes identified included 1. Motivations to join CCLADS 2. Challenges related to CCLADS initiation 3. Perceived facilitators for male participation in CCLADS, 4. Perceived barriers for male participation in CCLADS and 5. Proposed strategies for best implementation of CCLADs for better male engagement. Overall men liked the idea of CCLADs but they had preferences on how they should be implemented. Conclusion Men's enrollment into CCLADs is still low despite the benefits. Addressing the barriers to men's engagement and adopting proposed strategies may improve men's enrollment in CCLADS and thus improve their access to ART, Adherence and quality of life.